PENERAPAN SERTIFIKASI HALAL PADA PRODUK MAKANAN UMKM KABUPATEN SEKADAU - NIM. A1011221052, CALLISTA PUTRI VIANFIRNIE (Jurnal Fatwa Hukum, 2025)
Abstract This study highlights the urgency of halal certification as a form of consumer protection as well as an effort to improve the quality of food products produced by Micro, Small, and Medium Enterprises (MSMEs) in Sekadau Regency. Although business actors understand that halal labeling can increase consumer trust and enhance product competitiveness, the level of halal certification ownership remains low. This issue becomes increasingly significant with the enactment of Government Regulation Number 42 of 2024 as a derivative of Law Number 33 of 2014, which requires all circulating products to obtain halal assurance. Using an empirical method with a descriptive approach, this research collected data through observation, in-depth interviews, and documentation. The informants consisted of MSME actors and related institutions, including the Ministry of Religious Affairs of West Kalimantan Province, the Cooperative and MSME Office of Sekadau Regency, and Rumah BUMN PLN Sekadau. This approach provides a comprehensive overview of the implementation of halal certification and the challenges that arise at the regional level.The findings show that the implementation of halal certification for MSME food products is still very low. Out of 1,079 culinary MSMEs, only 35 have obtained certification, while 1,044 MSMEs have not yet fulfilled this obligation. MSMEs that have been certified experience significant benefits, such as increased consumer trust, expanded market reach, and greater income opportunities. However, most face obstacles including limited understanding of procedures, administrative difficulties, and constraints related to time and resources. MSMEs without certification also fail to comply with Articles 4 and 5 of Law Number 33 of 2014 and Government Regulation 42 of 2024, which require business actors to ensure the halal status of products before distribution. Therefore, enhancing outreach, providing integrated assistance, and improving access to certification services are strategic steps to encourage MSME compliance and ensure consumer protection and product competitiveness in Sekadau Regency going forward. Keywords: Consumer Protection, Halal Certification, MSMEs Abstrak Penelitian ini menyoroti urgensi sertifikasi halal sebagai bentuk perlindungan konsumen sekaligus upaya peningkatan kualitas produk makanan UMKM di Kabupaten Sekadau. Meskipun pelaku usaha memahami bahwa label halal mampu meningkatkan kepercayaan dan daya saing, tingkat kepemilikan sertifikasi masih rendah. Kondisi ini semakin signifikan dengan diberlakukannya PP Nomor 42 Tahun 2024 sebagai turunan dari UU Nomor 33 Tahun 2014, yang mewajibkan seluruh produk yang beredar memiliki jaminan halal. Dengan menggunakan metode empiris berpendekatan deskriptif, penelitian ini mengumpulkan data melalui observasi, wawancara mendalam, serta studi dokumentasi. Informan meliputi pelaku UMKM dan instansi terkait, seperti Kementerian Agama Provinsi Kalimantan Barat, Dinas Koperasi dan UMKM Kabupaten Sekadau, serta Rumah BUMN PLN Kabupaten Sekadau. Pendekatan ini memberikan gambaran menyeluruh mengenai implementasi sertifikasi halal serta hambatan yang muncul di tingkat daerah. Hasil penelitian menunjukkan bahwa pelaksanaan sertifikasi halal pada produk makanan UMKM masih sangat minim. Dari total 1.079 UMKM kuliner, hanya 35 UMKM yang telah bersertifikat, sementara 1.044 UMKM belum memenuhi kewajiban tersebut. UMKM yang telah bersertifikasi merasakan manfaat signifikan, antara lain meningkatnya kepercayaan konsumen, perluasan pasar, dan bertambahnya peluang pendapatan. Namun sebagian besar menghadapi hambatan berupa kurangnya pemahaman prosedur, kesulitan administrasi, serta keterbatasan waktu dan sumber daya. UMKM yang belum tersertifikasi belum mematuhi ketentuan Pasal 4 dan 5 UU Nomor 33 Tahun 2014 beserta PP 42 Tahun 2024, yang mewajibkan pelaku usaha memastikan kehalalan produk sebelum dipasarkan. Oleh karena itu, peningkatan sosialisasi, pendampingan terpadu, dan kemudahan akses layanan sertifikasi menjadi langkah strategis untuk mendorong kepatuhan UMKM serta memastikan perlindungan konsumen dan daya saing produk di Kabupaten Sekadau yang berkelanjutan ke depan. Kata Kunci: Perlindungan Konsumen, Sertifikasi Halal, UMKM